Starch metabolism in Leucoagaricus gongylophorus, the symbiotic fungus of leaf-cutting ants - Silva, A.; Bacci, M.; Pagnocca, F. C.; Bueno, O. C.; Hebling, M. J. A. (Elsevier B.V., 2006)
Leucoagaricus gongylophorus, the symbiotic fungus of the leaf-cutting ants, degrades starch, this degradation being supposed to occur in the plant material which leafcutters forage to the nests, generating most of the glucose which the ants utilize for food. In the present investigation, we show that laboratory cultures of L. gongylophorus produce extracellular alpha-amylase and maltase which degrade starch to glucose, reinforcing that the ants can obtain glucose from starch through the symbiotic fungus. Glucose was found to repress a-amylase and, more severely, maltase activity, thus repressing starch degradation by L. gongylophorus, so that we hypothesize that: (1) glucose down-regulation of starch degradation also occurs in the Atta sexdens fungus garden; (2) glucose consumption from the fungus garden by A. sexdens stimutates degradation of starch from plant material by L. gongylophorus, which may represent a mechanism by which Leafcutters can control enzyme production by the symbiotic fungus. Since glucose is found in the fungus garden inside the nests, down-regulation of starch degradation by glucose is supposed to occur in the nest and play a part in the control of fungal enzyme production by leafcutters. (c) 2005 Elsevier GmbH. All rights reserved.
Keywords: Leucoagaricus gongylophorus; Atta sexdens; enzymes induction; leaf-cutting ants; amylase